Cerebellar ataxia and Purkinje cell dysfunction caused by Ca 2+ -activated K + channel deficiency - Matthias Sausbier; Hua Hu; Claudia Arntz; Susanne Feil; S. Kamm; Helmuth Adelsberger; Ulrike Sausbier; Claudia A. Sailer; Robert Feil; Franz Hofmann; Michael Korth; Michael J. Shipston; et al. (2004)
Malfunctions of potassium channels are increasingly implicated as causes of neurological disorders. However, the functional roles of the large-conductance voltage- and Ca(2+)-activated K(+) channel (BK channel), a unique calcium, and voltage-activated potassium channel type have remained elusive. Here we report that mice lacking BK channels (BK(-/-)) show cerebellar dysfunction in the form of abnormal conditioned eye-blink reflex, abnormal locomotion and pronounced deficiency in motor coordination, which are likely consequences of cerebellar learning deficiency. At the cellular level, the BK(-/-) mice showed a dramatic reduction in spontaneous activity of the BK(-/-) cerebellar Purkinje neurons, which generate the sole output of the cerebellar cortex and, in addition, enhanced short-term depression at the only output synapses of the cerebellar cortex, in the deep cerebellar nuclei. The impairing cellular effects caused by the lack of postsynaptic BK channels were found to be due to depolarization-induced inactivation of the action potential mechanism. These results identify previously unknown roles of potassium channels in mammalian cerebellar function and motor control. In addition, they provide a previously undescribed animal model of cerebellar ataxia.